2020
DOI: 10.12973/ijem.6.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the Relationship between Metacognitive Awareness of Reading Strategies and Self-Efficacy Perception in Reading Comprehension in Mother-tongue: Sample of 8th Graders

Abstract: This study aims to identify the effect of metacognitive awareness of reading strategies on self-efficacy perception in reading comprehension of secondary school students and whether self-efficacy perception in reading comprehension of secondary school students differs according to the variables such as their gender and reading habits. In this correlational survey model study, data were collected from the sample of 380 students of 8th grade by using 'Metacognitive Awareness of Reading Strategies Inventory' deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In connection, Muhid et al (2020) and Thongwichit and Buripakdi (2021) had proven that metacognitive strategies have shown usefulness in reading comprehension, to the extent that they show self-knowledge, which means that they know how to choose what reading strategies are helpful in their reading (Bagci & Unveren, 2020). Öztürk and Aydogmus (2021) further explained that these metacognitive strategies are not only used while reading but even employ before and after reading, considering that it is a process of comprehension.…”
Section: Reading Strategiesmentioning
confidence: 98%
See 2 more Smart Citations
“…In connection, Muhid et al (2020) and Thongwichit and Buripakdi (2021) had proven that metacognitive strategies have shown usefulness in reading comprehension, to the extent that they show self-knowledge, which means that they know how to choose what reading strategies are helpful in their reading (Bagci & Unveren, 2020). Öztürk and Aydogmus (2021) further explained that these metacognitive strategies are not only used while reading but even employ before and after reading, considering that it is a process of comprehension.…”
Section: Reading Strategiesmentioning
confidence: 98%
“…Simply put, metacognition is thinking about thinking (Zhang & Zheng, 2020;Bagci & Unveren, 2020) and learning (Safia & Ghania, 2020). Safia and Shania (2020) emphasized that metacognition takes part while there are reading comprehension matters.…”
Section: Reading Comprehension and Metacognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of reading strategies spread over many dimensions ( Al-Mekhlafi, 2018 ; Bagci & Unveren, 2020 ; Deliany & Cahyono, 2020 ; Deliany & Cahyono, 2020 ; Suraprajit, 2019 ; Wahyono, 2019 ; Al-Ahdal & Al-Awaid, 2014 ). Wahyono (2019) explored the correlations between reading strategies and reading comprehension while Deliany and Cahyono (2020) investigated EFL students’ use of metacognitive reading strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reading strategies have been the focus of many previous studies ( Al-Mekhlafi, 2018 ; Bagci & Unveren, 2020 ; Deliany & Cahyono, 2020 ; Deliany & Cahyono, 2020 ; Suraprajit, 2019 ; Wahyono, 2019 ; Al-Ahdal & Almarshedi, 2022 ). For example, Deliany and Cahyono (2020) studied EFL students’ implementation of metacognitive reading tactics and reported that most students had high metacognitive reading strategies.…”
Section: Literature Reviewmentioning
confidence: 99%